Wood-based hydrophobic low-voltage electric heating composite material and preparation method thereof

By using multiple synergistic composite technologies of graphitized conductive carbonized wood, MXene loaded graphene and hydrophobic modified epoxy resin in wood electrothermal composite materials, the problem of electrical safety and conductive network damage during long-term use of wood electrothermal composite materials is solved. It achieves ultra-low voltage, high-efficiency electric heating, ultra-hydrophobic and high thermal conductivity.

CN119407900APending Publication Date: 2025-02-11INST OF WOOD INDUDTRY CHINESE ACAD OF FORESTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643326.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Wooden electric heating composite materials are prone to separation of the bonding interface between conductive units and wood materials under long-term power-on, hot and cold cycles and temperature-humidity alternating field environments, and there are electrical safety problems of short circuit or local high temperatures, and conductive materials are prone to electricity-humidity and heat-bearing. damage.

Method used

Through multivariate synergistic effect, graphitized conductive carbonized wood is used as the frame, combined with MXene-loaded graphene as the heating and thermal conductivity unit, and hydrophobic modified epoxy resin as the glue, it is prepared to produce ultra-low voltage electrothermal effect, superhydrophobic and Wooden electric thermal composite material with high thermal conductivity.

Benefits of technology

It achieves high-efficiency electric heating effect under ultra-low voltage, has superhydrophobic properties and high thermal conductivity, and has good flame retardant properties, solving the problems of electrical safety and conductive network damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407900A_ABST
    Figure CN119407900A_ABST
Patent Text Reader

Abstract

The invention provides a wood-based hydrophobic low-voltage electric heating composite material and a preparation method thereof. The wood-based hydrophobic low-voltage electric heating composite material with an ultra-low-voltage electric heating effect, super-hydrophobicity and high heat-conducting property is obtained through a multi-element synergistic effect. Loading nano nickel oxide on the surface of the delignification wood, and graphitizing under oxidation catalysis of the nano nickel oxide to obtain conductive carbonized wood; performing etching treatment on Ti3AlC2 by using an etching solution prepared by mixing lithium fluoride and hydrochloric acid to obtain an etching mixture; centrifugally deacidifying the etching mixture, and collecting supernate to obtain an MXene suspension; adding graphene into the suspension, carrying out water bath ultrasonic dispersion and magnetic stirring, and drying to obtain an MXene loaded graphene mixture; adding the mixture into a perfluorooctyltrichlorosilane modified epoxy resin adhesive, then adding a curing agent, mixing, and defoaming to obtain an MXene / graphene-epoxy resin mixture; the conductive carbonized wood is pressurized, impregnated and cured by the mixture to obtain the wood-based hydrophobic low-voltage electric heating composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to electrothermal composite material technology, and in particular to a wood-based hydrophobic low-voltage electrothermal composite material and a preparation method thereof. Background Art

[0002] Electrothermal composite materials are an important application branch of conductive materials. When voltage is applied to electrothermal composite materials, the internal conductive units can convert electrical energy into thermal energy due to the Joule heating effect after power is turned on, thereby playing the role of a heater. Among electrothermal composite materials, wood electrothermal composite materials use conductive materials as heating elements, which are composited with wood matrix through resin adhesives to form a type of functional material with heating function, giving wood materials electric heating function. It belongs to low-temperature radiant electric heating technology and has the function of integrating heating and decoration. However, under long-term power supply, hot and cold cycles, and alternating temperature and humidity fields, electric heating and moist heat can easily cause separation of the bonding interface between the conductive unit and the wood material, resulting in electrical safety issues such as short circuits or local high temperatures. In addition, due to the different resistive thermal effects exhibited by the different matrix materials and conductive fillers, when the internal conductive network in the matrix is ​​subjected to long-term electro-moisture heat, the internal conductive network will be seriously affected, resulting in electro-thermal damage to the conductive material, or the conductive network will be destroyed due to the entry of moisture. Therefore, the development of electric heating elements that produce efficient electric heating effects under ultra-low voltage and have good thermal conductivity and waterproof properties is a key way to solve the problem of long-term safe application of wood-based electrothermal composite materials in hot and cold cycles. Summary of the invention

[0003] The present invention is developed in view of the above problems, and its purpose is to provide a wood-based hydrophobic low-voltage electrothermal composite material and a preparation method thereof, so as to obtain a wood-based electrothermal composite material with ultra-low voltage electrothermal effect, super hydrophobicity and high thermal conductivity through multi-component synergistic effect.

[0004] The first aspect of the present invention relates to a method for preparing a wood-based hydrophobic low-voltage electrothermal composite material, which comprises:

[0005] (1) adjusting the pH value of a 4-6 wt% NaClO2 aqueous solution to 4.8-5.2 by using 17-18 mol / L glacial acetic acid, immersing wood in the adjusted NaClO2 aqueous solution, wherein the material-liquid mass ratio is 1:(100-150), then treating the wood in a water bath at 80-85° C. for 5-7 h, taking the wood out, washing, and drying the wood to obtain delignified wood;

[0006] (2) immersing the delignified wood in a nano-nickel oxide / acetone dispersion, wherein the mass ratio of the material to the liquid is 1:(100-180), and the mass ratio of the nano-nickel oxide to the acetone is (8-10):(90-92), and then immersing the wood in a sealed state for 30-50 minutes to load the nano-nickel oxide on the surface of the wood, and then taking it out and drying it until the acetone is completely volatilized;

[0007] (3) heating the nano-nickel oxide-loaded wood to a carbonization temperature of 300 to 500° C. at a rate of 5 to 7° C. / min under nitrogen protection for 20 to 30 min, so that the wood is graphitized under the oxidative catalytic action of the nano-nickel oxide to obtain conductive carbonized wood;

[0008] (4) slowly adding Ti3AlC2 powder to an etching solution under vigorous stirring, wherein the mass ratio of the material to the liquid is (1-1.5):(10-12), wherein the etching solution is prepared by adding lithium fluoride to hydrochloric acid having a concentration of 11-13 mol / L, and the material-liquid ratio of lithium fluoride to hydrochloric acid is (2-4) g:(20-40) ml, and then etching is performed at a temperature of 45-50° C. for 24-36 hours to obtain an etching mixture;

[0009] (5) The etching mixture is centrifuged and washed multiple times to remove the acid, and after each centrifugation, it is layered by vigorous shaking, and the supernatant after each layering is collected to collect the exfoliated MXene suspension;

[0010] (6) adding graphene powder to the MXene suspension at a material-liquid mass ratio of 1:(50-80), then performing water bath ultrasonic dispersion for 30-40 min and magnetic stirring for 8-12 h, and drying to obtain a MXene-loaded graphene mixture;

[0011] (7) adding the MXene-loaded graphene mixture to the 1H,1H,2H,2H-perfluorooctyltrichlorosilane modified epoxy resin adhesive and stirring at high speed to uniformly mix, then adding a curing agent for high-speed shear mixing, and then removing bubbles from the mixture to obtain a MXene / graphene-epoxy resin mixture, wherein the 1H,1H,2H,2H-perfluorooctyltrichlorosilane modified epoxy resin adhesive is prepared by mixing 1H,1H,2H,2H-perfluorooctyltrichlorosilane and epoxy resin adhesive in a mass ratio of 1:(15-20), wherein the epoxy resin solid content in the epoxy resin adhesive is 55-58%, the viscosity is 500-700 mPa.s, and the mass ratio of the MXene-loaded graphene mixture, the 1H,1H,2H,2H-perfluorooctyltrichlorosilane modified epoxy resin adhesive and the curing agent is (2-10):(85-92):(5-6);

[0012] (8) The conductive carbonized wood is subjected to negative pressure treatment with a vacuum degree of 0.1 to 0.15 MPa for 10 to 15 min, and then the MXene / graphene-epoxy resin mixture is added while maintaining the negative pressure until the wood is submerged, with a mass ratio of (5 to 20):(50 to 100), and then vacuum pressure impregnation is performed with a pressure of 1.0 to 1.2 MPa for 30 to 60 min. After being taken out, the mixture is cured at room temperature to obtain a wood-based hydrophobic low-voltage electrothermal composite material.

[0013] Furthermore, in (2), the particle size of nano nickel oxide is 20 to 60 nm.

[0014] Furthermore, in (4), the particle size of the Ti3AlC2 powder is 0.5 to 25 μm.

[0015] Furthermore, in (4), Ti3AlC2 powder is added to the etching solution at a rate of 0.1 g / 10 s.

[0016] Furthermore, in said (4), the violent stirring speed is 10000 to 12000 rpm / min.

[0017] Furthermore, the step (4) is carried out in an acid-resistant container.

[0018] Furthermore, in (4), the density of hydrochloric acid is (1.1-1.3) g / mL.

[0019] Furthermore, in (5), a high-speed centrifuge is used to add deionized water to perform centrifugal washing and acid removal for more than 5 times, the centrifugal speed is 8000-10000 rpm / min, and each centrifugal treatment is 5-6 minutes.

[0020] Furthermore, in (5), the violent oscillation frequency is 0.05 to 0.1 Hz, and the amplitude is 100 to 150 μm.

[0021] Furthermore, in (6), the graphene powder has a particle size of 1 to 6 μm and a thickness of 1 to 4 nm.

[0022] Furthermore, in (6), the ultrasonic frequency is 120-130 kHz, and the magnetic stirring speed is 800-1500 rpm / min.

[0023] Furthermore, in (7), the high-speed stirring speed is 3000 to 5000 rpm / min.

[0024] Furthermore, in (7), the high-speed shearing speed is 2000-4000 rpm / min, the working head diameter is 90-100 mm, and the time is 10-20 min.

[0025] Furthermore, in (7), the curing agent is an ammonia-modified curing agent, and further, the ammonia-modified curing agent is SH-K700, with a melting point of 160 to 180° C. and a particle size of 4.5 to 5.5 μm.

[0026] Furthermore, in (7), air bubbles are removed by using a vacuum oven.

[0027] Furthermore, in said (8), curing is carried out at room temperature for more than 12 hours.

[0028] The wood used is basswood, with a density of 0.55-0.62 g / cm 3 , thickness 0.25 ~ 4.0mm, surface resistance 0.15 ~ 0.22Ω / cm after nano nickel oxide catalytic carbonization.

[0029] The second aspect of the present invention relates to a wood-based hydrophobic low-voltage electrothermal composite material, which is prepared by any of the above-mentioned preparation methods.

[0030] The present invention utilizes the synergistic conductive heating advantages between different types of nano-micron conductive materials to improve the electrical and thermal performance of the composite material. In particular, the conductive carbonized wood after graphitization is used as a frame, and the high specific surface area, excellent electrical conductivity, and chemically active surface advantages of transition metal carbides are used as fillers to coordinate with different types of nanomaterials to enhance the electrical and thermal conductivity of the composite material.

[0031] The present invention uses carbonized delignified basswood as a frame, MXene-loaded graphene as a heating and thermal conductive unit, and hydrophobically modified epoxy resin as a glue, and prepares a wood electrothermal composite material with ultra-low voltage electrothermal effect, super hydrophobicity and high thermal conductivity through multi-component synergistic composite.

[0032] By embedding graphene in the Mxene layer, the conductive path between the Mxene layers obtains a bridging effect, which is more conducive to electron transmission, forming a more efficient and continuous conductive channel, and improving the electrothermal response efficiency of the electrothermal element. At the same time, the graphitized wood frame further improves the continuity of the conductive channel at the macro level, avoiding the disadvantage of the traditional wood frame being non-conductive.

[0033] In terms of flame retardancy, delignified wood is conducive to the penetration of epoxy resin adhesive into the multi-tube pores of wood to form glue nails, forming a blocked carbon layer during the combustion process, reducing the combustion cavity of the wood itself. In addition, during combustion, nano / micron-scale fillers and carbonized wood fibers present a multi-component complex interface to form a complex multi-carbon layer structure, which can correspond to different combustion states. In addition, the embedded graphene in Mxene also improves the density of the carbon layer formation, enhancing the flame retardant effect from the microscopic interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a temperature-time variation curve diagram of the electrothermal composite material prepared in Example 1 according to an embodiment of the present invention after being tested.

[0035] Figure 2 This is a color temperature diagram of the tested electrothermal composite material of Preparation Example 1 according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] In the process description of the present invention, there will be some numerical values ​​related to temperature or pressure, process change rate, etc. For example, taking temperature as an example, those skilled in the art should know that when it is mentioned that the actual meaning of carrying out a reaction at a certain temperature is that the control of temperature is not an absolute constant temperature, but may or even often will have a certain fluctuation, which may exceed one degree or even more in some cases, as long as the implementation purpose can be achieved. The amplitude of temperature change and the accuracy of temperature control are based on the scope that can be understood by those skilled in the art.

[0037] In addition, the temperature defined herein may be the input for temperature control on the equipment used, and the temperature at a certain point in the actual process depends on the particularity of the equipment and the reaction conditions at the time. The defined temperature may also be the target of the operator's instruction, which may involve a temperature change time in actual control, or even a process of repeated ups and downs. For example, when the temperature is detected to be lower than the defined temperature, the reactor is heated, and when it is higher than the defined temperature, the reactor is cooled, so as to maintain the command temperature as a whole.

[0038] When the concept of normal temperature or room temperature is mentioned, it usually refers to 22-25°C, and sometimes it may be between 20-28°C depending on the process. 25°C is used in the implementation of the present invention, but it should be considered that the above temperature range can achieve the corresponding effect. In actual industry, different fields have different understandings of normal temperature or room temperature, but from the perspective of the implementation and application of patent law, it should be viewed as limited to achieving the purpose of the invention, and should not be limited to the narrow experience range of a certain field.

[0039] In the present invention, if there is no temperature or room temperature limit mentioned for some processes, it should generally be considered that they are carried out at normal temperature or room temperature. Those skilled in the art can control the process conditions without special understanding, unless otherwise specified or those skilled in the art should understand the special details.

[0040] In the present invention, unless otherwise stated, the numerical range "A to B" means greater than A (greater than or equal to A) and less than B (less than or equal to B).

[0041] Preparation Example 1:

[0042] 1. Prepare a 5wt% NaClO2 solution with distilled water, and adjust the pH value to 5.0 with 17.5mol / L glacial acetic acid. Soak a 60mm×30mm×0.25mm natural basswood piece in the acid-adjusted NaClO2 solution, with a material-liquid mass ratio of 1:100. The density of basswood is 0.6g / cm 3 , thickness 0.25mm, after being treated in a water bath at 80°C for 5h, taken out, washed with distilled water, and dried for use to obtain delignified basswood.

[0043] 2. Using nano nickel oxide as an oxidation catalyst, add 20 nm nickel oxide powder into acetone to prepare a nickel oxide acetone dispersion with a nickel oxide content of 8 wt%. Soak delignified basswood in the nickel oxide acetone dispersion at a material-liquid mass ratio of 1:100, and soak in a closed state for 30 minutes to load nano nickel oxide on the surface of the basswood cell cavity, take out and dry, and wait for the acetone to completely evaporate.

[0044] 3. The basswood chips loaded with nano-nickel oxide were loaded into an alumina crucible, placed in a high-temperature tube furnace, and carbonized under nitrogen protection. The nitrogen flow rate was first turned on and controlled at 250 mL / min, maintained for 30 minutes, and after the internal gas was evacuated, the temperature was raised to 300°C at a rate of 5°C / min for carbonization treatment for 20 minutes. The basswood chips were graphitized under the catalytic action of the oxidant nano-nickel oxide to obtain carbonized basswood chips. The surface resistance after nano-nickel oxide catalytic carbonization was 0.2Ω / cm.

[0045] 4. In a high-density polyethylene container, add lithium fluoride to 12 mol / L hydrochloric acid with a density of 1.2 g / mL to prepare an etching solution, with a material-liquid ratio of 2 g / 20 mL. Slowly add 0.5 μm Ti3AlC2 powder as a precursor to the etching solution under vigorous stirring at a speed of 10000 rpm / min, with a material-liquid mass ratio of 1:10. Etch Ti3AlC2 at 45°C for 24 hours.

[0046] 5. The etched MXene mixture was washed with deionized water for 5 times to remove excess acid in a high-speed centrifuge at a speed of 10,000 rpm / min, with each cycle lasting 5 minutes. After each centrifugation, the etched MXene was stratified by vigorous shaking at a frequency of 0.05 Hz and an amplitude of 100 μm. The exfoliated MXene suspension was collected by collecting the supernatant of multiple centrifugation cycles.

[0047] 6. Add graphene powder with a particle size of 1 μm and a thickness of 1 nm into the MXene suspension with a material-liquid mass ratio of 1:50, perform ultrasonic dispersion in a water bath for 30 min, and perform magnetic stirring for 8 h. The ultrasonic frequency is 120 KHz and the magnetic stirring speed is 800 rpm / min to obtain a MXene-loaded graphene solid-liquid mixture, which is then dried to obtain a MXene-loaded graphene mixture.

[0048] 7. Add 1H,1H,2H,2H-perfluorooctyltrichlorosilane (C8H4Cl3F13Si>97.0%) to the epoxy resin with a mass ratio of 1:15, an epoxy resin solid content of 55%, and a viscosity of 500mPa.s. The epoxy resin is hydrophobically modified by 1H,1H,2H,2H-perfluorooctyltrichlorosilane. A MXene-loaded graphene mixture with a mass ratio of 2:92 was added to a hydrophobically modified epoxy resin and stirred at a high speed (speed 3000 rpm / min) for uniform mixing. Then, an ammonia-modified curing agent SH-K700 (melting point 160°C, particle size 4.5 μm) with a mass ratio of 6wt% was added to the MXene / graphene-epoxy resin. The mixture was mixed by high-speed shearing (high-speed shearing speed of 2000 rpm / min, working head diameter 90 mm) for 10 minutes to prepare a MXenes / graphene-epoxy resin mixed material. The mixed material was placed in a vacuum oven for 10 minutes to remove bubbles. A vacuum oven was used to ensure that the material properties, such as water loss, were controlled to be negligible to obtain a MXene / graphene-epoxy resin mixture.

[0049] 8. Place the MXene / graphene-epoxy resin mixed material in a high-pressure impregnation pot, immerse the carbonized basswood chips in the MXene / graphene-epoxy resin mixed material with a mass ratio of 5:50, and use the vacuum pressurization method for impregnation. Perform vacuum treatment before pressurization, and use the negative pressure in the impregnation pot to extract the air inside the conductive carbonized wood. The vacuum degree is 0.1 MPa, and the time is 10 minutes. Then, perform pressurized impregnation with a pressure of 1.0 MPa for 0.5 hours. After unloading the pressure, take it out and cure it at room temperature for 12 hours to obtain a wood-based hydrophobic low-voltage electric heating composite material.

[0050] 9. The prepared electrothermal composite material has an ultra-low voltage electrothermal effect, such as Figure 1 The applied voltage is 2-4V, the steady-state temperature is 50-119°C, the contact angle of the wood electrothermal composite material is 145-156°, and it has super hydrophobic properties. At the same time, the synergistic effect of MXene and graphene significantly improves the thermal conductivity of the material, with a thermal conductivity coefficient of 0.56-0.72W / (mK). In addition, it has good flame retardant properties, and the first heat release rate peak is 72.78kW / m 2 , oxygen index 36.7.

[0051] Preparation Example 2:

[0052] 1. Prepare a 4wt% NaClO2 solution with distilled water, and adjust the pH value to 4.5 with 17mol / L glacial acetic acid. Soak a 60mm×30mm×1.0mm natural basswood piece in the acid-adjusted NaClO2 solution, with a material-liquid mass ratio of 1:120. The density of basswood is 0.55g / cm 3, thickness 1.0mm, treated in a water bath at 85°C for 6h, taken out, washed with distilled water, and dried for use to obtain delignified basswood.

[0053] 2. Using nano nickel oxide as an oxidation catalyst, add 40 nm nickel oxide powder into acetone to prepare a nickel oxide acetone dispersion with a nickel oxide content of 9 wt%. Soak delignified basswood in the nickel oxide acetone dispersion at a material-liquid mass ratio of 1:120, and soak in a closed state for 50 minutes to load the surface of the basswood cell cavity with nano nickel oxide, then take out and dry until the acetone is completely volatilized.

[0054] 3. The basswood chips loaded with nano-nickel oxide were loaded into an alumina crucible, placed in a high-temperature tube furnace, and carbonized under nitrogen protection. The nitrogen flow rate was first turned on and controlled at 250 mL / min, maintained for 30 minutes, and after the internal gas was evacuated, the temperature was raised to 400°C at a rate of 6°C / min for carbonization treatment for 30 minutes. The basswood chips were graphitized under the catalytic action of the oxidant nano-nickel oxide to obtain carbonized basswood chips. The surface resistance after nano-nickel oxide catalytic carbonization was 0.15Ω / cm.

[0055] 4. In a high-density polyethylene container, add lithium fluoride to 13 mol / L hydrochloric acid with a density of 1.3 g / mL to prepare an etching solution, with a material-liquid ratio of 2 g / 40 mL. Slowly add 1.5 μm Ti3AlC2 powder as a precursor to the etching solution under vigorous stirring at a speed of 12000 rpm / min, with a material-liquid mass ratio of 1.5:10. Etch Ti3AlC2 at 50°C for 30 hours.

[0056] 5. The etched MXene mixture was washed with deionized water for 5 times to remove excess acid in a high-speed centrifuge at a speed of 8000 rpm / min, with each cycle lasting 6 minutes. After each centrifugation, the etched MXene was layered by vigorous shaking at a frequency of 0.1 Hz and an amplitude of 120 μm. The exfoliated MXene suspension was collected by collecting the supernatant of multiple centrifugation cycles.

[0057] 6. Add graphene powder with a particle size of 3 μm and a thickness of 2 nm into the MXene suspension with a material-liquid mass ratio of 1:60, perform ultrasonic dispersion in a water bath for 30 min, and magnetically stir for 10 h. The ultrasonic frequency is 130 KHz and the magnetic stirring speed is 1000 rpm / min to obtain a MXene-loaded graphene solid-liquid mixture, which is then dried to obtain a MXene-loaded graphene mixture.

[0058] 7. Add 1H,1H,2H,2H-perfluorooctyltrichlorosilane (C8H4Cl3F13Si>97.0%) to the epoxy resin with a mass ratio of 1:16, an epoxy resin solid content of 56%, and a viscosity of 600mPa.s. The epoxy resin is hydrophobically modified by 1H,1H,2H,2H-perfluorooctyltrichlorosilane. A MXene-loaded graphene mixture with a mass ratio of 10:85 was added to a hydrophobically modified epoxy resin and stirred at a high speed (speed 4000 rpm / min) for uniform mixing. Then, an ammonia-modified curing agent SH-K700 (melting point 170°C, particle size 5.0 μm) with a mass ratio of 5wt% was added to the MXene / graphene-epoxy resin. The mixture was mixed by high-speed shearing (high-speed shearing speed of 1500 rpm / min, working head diameter of 100 mm) for 20 minutes to prepare a MXenes / graphene-epoxy resin mixed material. The mixed material was placed in a vacuum oven for 10 minutes to remove bubbles. A vacuum oven was used to ensure that the material properties, such as water loss, were controlled to be negligible to obtain a MXene / graphene-epoxy resin mixture.

[0059] 8. Place the MXene / graphene-epoxy resin mixed material in a high-pressure impregnation pot, immerse the carbonized basswood chips in the MXene / graphene-epoxy resin mixed material at a mass ratio of 5:100, and use the vacuum pressurization method for impregnation. Perform vacuum treatment before pressurization, and use the negative pressure in the impregnation pot to extract the air inside the conductive carbonized wood. The vacuum degree is 0.15 MPa, and the time is 12 minutes. Then, perform pressurized impregnation at a pressure of 1.1 MPa for 40 minutes. After unloading the pressure, take it out and cure it at room temperature for 15 hours to obtain a wood-based hydrophobic low-voltage electric heating composite material.

[0060] 9. The prepared electrothermal composite material has an ultra-low-voltage electrothermal effect. The applied voltage is 2-4V and the steady-state temperature is 57-112°C. The contact angle of the wood electrothermal composite material is 149-157°, and it has super-hydrophobic properties. At the same time, due to the synergistic effect of MXene and graphene, the thermal conductivity of the material is significantly improved, and the thermal conductivity coefficient is 0.61-0.77W / (mK). In addition, it has good flame retardant properties, and the first heat release rate peak is 67.73kW / m 2 , oxygen index 37.8.

[0061] Preparation Example 3:

[0062] 1. Prepare a 6wt% NaClO2 solution with distilled water, and adjust the pH value to 5.5 with 18mol / L glacial acetic acid. Soak a 60mm×30mm×4.0mm natural basswood piece in the acid-adjusted NaClO2 solution, with a material-liquid mass ratio of 1:140. The density of basswood is 0.62g / cm 3, thickness 4.0mm, treated in a water bath at 82°C for 7h, taken out, washed with distilled water, and dried for use to obtain delignified basswood.

[0063] 2. Using nano nickel oxide as an oxidation catalyst, add 50 nm nickel oxide powder into acetone to prepare a nickel oxide acetone dispersion with a nickel oxide content of 10 wt%. Soak delignified basswood in the nickel oxide acetone dispersion at a material-liquid mass ratio of 1:160, and soak in a closed state for 40 minutes to load nano nickel oxide on the surface of the basswood cell cavity, take out and dry, and wait for the acetone to completely evaporate.

[0064] 3. The basswood chips loaded with nano-nickel oxide were loaded into an alumina crucible, placed in a high-temperature tube furnace, and carbonized under nitrogen protection. The nitrogen flow rate was first turned on and controlled at 250 mL / min, maintained for 30 minutes, and after the internal gas was evacuated, the temperature was raised to 300°C at a rate of 7°C / min for carbonization treatment for 20 minutes. The basswood chips were graphitized under the catalytic action of the oxidant nano-nickel oxide to obtain carbonized basswood chips. The surface resistance after nano-nickel oxide catalytic carbonization was 0.22Ω / cm.

[0065] 4. In a high-density polyethylene container, add lithium fluoride to 11 mol / L hydrochloric acid with a density of 1.1 g / mL to prepare an etching solution, with a material-liquid ratio of 4 g / 20 mL. Slowly add 2 μm Ti3AlC2 powder as a precursor to the etching solution under vigorous stirring at a speed of 10000 rpm / min, with a material-liquid mass ratio of 1:12. Etch Ti3AlC2 at 50°C for 30 hours.

[0066] 5. The etched MXene mixture was washed with deionized water for 5 times to remove excess acid in a high-speed centrifuge at a speed of 9000 rpm / min, with each cycle lasting 6 minutes. After each centrifugation, the etched MXene was layered by vigorous shaking at a frequency of 0.1 Hz and an amplitude of 140 μm. The exfoliated MXene suspension was collected by collecting the supernatant of multiple centrifugation cycles.

[0067] 6. Add graphene powder with a particle size of 5 μm and a thickness of 3 nm into the MXene suspension with a material-liquid mass ratio of 1:70, perform ultrasonic dispersion in a water bath for 40 min, and perform magnetic stirring for 12 h. The ultrasonic frequency is 130 KHz and the magnetic stirring speed is 1200 rpm / min to obtain a MXene-loaded graphene solid-liquid mixture, which is then dried to obtain a MXene-loaded graphene mixture.

[0068] 7. Add 1H,1H,2H,2H-perfluorooctyltrichlorosilane (C8H4Cl3F13Si>97.0%) to the epoxy resin with a mass ratio of 1:17, an epoxy resin solid content of 57%, and a viscosity of 700m Pa.s. The epoxy resin is hydrophobically modified by perfluorooctyltrichlorosilane. A MXene-loaded graphene mixture with a mass ratio of 4:91 was added to a hydrophobically modified epoxy resin and stirred at a high speed (speed 4000 rpm / min) for uniform mixing. Then, an ammonia-modified curing agent SH-K700 (melting point 180°C, particle size 5.5 μm) with a mass ratio of 5wt% was added to the MXene / graphene-epoxy resin. The mixture was mixed for 10 minutes by high-speed shear (high-speed shear speed of 2500 rpm / min, working head diameter of 100 mm) to prepare a MXenes / graphene-epoxy resin mixed material. The mixed material was placed in a vacuum oven for 10 minutes to remove bubbles. A vacuum oven was used to ensure that the material properties, such as moisture loss, were controlled to be negligible to obtain a MXene / graphene-epoxy resin mixture.

[0069] 8. Place the MXene / graphene-epoxy resin mixed material in a high-pressure impregnation pot, immerse the carbonized basswood chips in the MXene / graphene-epoxy resin mixed material with a mass ratio of 20:50, and use the vacuum pressure method for impregnation. Vacuum treatment is performed before pressurization. The negative pressure in the impregnation pot is used to extract the air inside the conductive carbonized wood. The vacuum degree is 0.1 MPa and the time is 12 minutes. Then, pressurized impregnation is performed with a pressure of 1.2 MPa for 50 minutes. After unloading the pressure, take it out and cure it at room temperature for 18 hours to obtain a wood-based hydrophobic low-voltage electric heating composite material.

[0070] 9. The prepared electrothermal composite material has an ultra-low-voltage electrothermal effect. The applied voltage is 2-4V and the steady-state temperature is 46-109°C. The contact angle of the wood electrothermal composite material is 148-156°, and it has super-hydrophobic properties. At the same time, due to the synergistic effect of MXene and graphene, the thermal conductivity of the material is significantly improved, and the thermal conductivity coefficient is 0.49-0.70W / (mK). In addition, it has good flame retardant properties, and the first heat release rate peak is 65.81kW / m 2 , oxygen index 37.9.

[0071] Preparation Example 4:

[0072] 1. Prepare a 5wt% NaClO2 solution with distilled water, and adjust the pH value to 5.0 with 17.5mol / L glacial acetic acid. Soak a 60mm×30mm×2.0mm natural basswood piece in the acid-adjusted NaClO2 solution, with a material-liquid mass ratio of 1:150. The density of basswood is 0.6g / cm 3 , thickness 2.0mm, treated in a water bath at 80°C for 5h, taken out, washed with distilled water, and dried for use to obtain delignified basswood.

[0073] 2. Using nano nickel oxide as an oxidation catalyst, add 30 nm nickel oxide powder into acetone to prepare a nickel oxide acetone dispersion with a nickel oxide content of 8 wt%. Soak delignified basswood in the nickel oxide acetone dispersion at a material-liquid mass ratio of 1:180, and soak for 30 minutes in a closed state so that the surface of the basswood cell cavity is loaded with nano nickel oxide, then take out and dry until the acetone is completely volatilized.

[0074] 3. The basswood chips loaded with nano-nickel oxide were loaded into an alumina crucible, placed in a high-temperature tube furnace, and carbonized under nitrogen protection. The nitrogen flow rate was first turned on and controlled at 250 mL / min, maintained for 30 minutes, and after the internal gas was evacuated, the temperature was raised to 400°C at a rate of 5°C / min for carbonization treatment for 20 minutes. The basswood chips were graphitized under the catalytic action of the oxidant nano-nickel oxide to obtain carbonized basswood chips. The surface resistance after nano-nickel oxide catalytic carbonization was 0.18Ω / cm.

[0075] 4. In a high-density polyethylene container, add lithium fluoride to 12 mol / L hydrochloric acid with a density of 1.2 g / mL to prepare an etching solution, with a material-liquid ratio of 2.5 g / 30 mL. Slowly add 25 μm Ti3AlC2 powder as a precursor to the etching solution under vigorous stirring at a speed of 11000 rpm / min, with a material-liquid mass ratio of 1.5:12. Etch Ti3AlC2 at 45°C for 36 hours.

[0076] 5. The etched MXene mixture was washed with deionized water for 5 times to remove excess acid in a high-speed centrifuge at a speed of 10,000 rpm / min, with each cycle lasting 5 minutes. After each centrifugation, the etched MXene was layered by vigorous shaking at a frequency of 0.05 Hz and an amplitude of 150 μm. The exfoliated MXene suspension was collected by collecting the supernatant of multiple centrifugation cycles.

[0077] 6. Add graphene powder with a particle size of 6 μm and a thickness of 4 nm into the MXene suspension with a material-liquid mass ratio of 1:80, perform ultrasonic dispersion in a water bath for 30 min, and magnetically stir for 8 h. The ultrasonic frequency is 120 KHz and the magnetic stirring speed is 1500 rpm / min to obtain a MXene-loaded graphene solid-liquid mixture, which is then dried to obtain a MXene-loaded graphene mixture.

[0078] 7. Add 1H,1H,2H,2H-perfluorooctyltrichlorosilane (C8H4Cl3F13Si>97.0%) to the epoxy resin with a mass ratio of 1:18, an epoxy resin solid content of 58%, and a viscosity of 700mPa.s. The epoxy resin is hydrophobically modified by perfluorooctyltrichlorosilane. A MXene-loaded graphene mixture with a mass ratio of 6:88 was added to a hydrophobically modified epoxy resin and stirred at a high speed (speed 3000 rpm / min) for uniform mixing. Then, an ammonia-modified curing agent SH-K700 (melting point 160°C, particle size 4.5 μm) with a mass ratio of 6wt% was added to the MXene / graphene-epoxy resin. The mixture was mixed by high-speed shearing (high-speed shearing speed of 4000 rpm / min, working head diameter of 100 mm) for 10 minutes to prepare a MXenes / graphene-epoxy resin mixed material. The mixed material was placed in a vacuum oven for 10 minutes to remove bubbles. A vacuum oven was used to ensure that the material properties, such as water loss, were controlled to be negligible to obtain a MXene / graphene-epoxy resin mixture.

[0079] 8. Place the MXene / graphene-epoxy resin mixed material in a high-pressure impregnation pot, immerse the carbonized basswood chips in the MXene / graphene-epoxy resin mixed material with a mass ratio of 20:100, and use the vacuum pressure method for impregnation. Perform vacuum treatment before pressurization, and use the negative pressure in the impregnation pot to extract the air inside the conductive carbonized wood. The vacuum degree is 0.1 MPa, and the time is 15 minutes. Then, perform pressurized impregnation with a pressure of 1.0 MPa for 0.5 hours. After unloading the pressure, take it out and cure it at room temperature for 20 hours to obtain a wood-based hydrophobic low-voltage electric heating composite material.

[0080] 9. The prepared electrothermal composite material has an ultra-low-voltage electrothermal effect. The applied voltage is 2-4V and the steady-state temperature is 57-117°C. The contact angle of the wood electrothermal composite material is 148-157°, and it has super-hydrophobic properties. At the same time, due to the synergistic effect of MXene and graphene, the thermal conductivity of the material is significantly improved, and the thermal conductivity coefficient is 0.57-0.81W / (mK). In addition, it has good flame retardant properties, and the first heat release rate peak is 65.21kW / m 2 , oxygen index 38.1.

[0081] Preparation Example 5:

[0082] 1. Prepare a 5wt% NaClO2 solution with distilled water, and adjust the pH value to 5.0 with 17.5mol / L glacial acetic acid. Soak a 60mm×30mm×0.25mm natural basswood piece in the acid-adjusted NaClO2 solution, with a material-liquid mass ratio of 1:150. The density of basswood is 0.6g / cm 3 , thickness 0.25mm, after being treated in a water bath at 80°C for 5h, taken out, washed with distilled water, and dried for use to obtain delignified basswood.

[0083] 2. Using nano nickel oxide as an oxidation catalyst, add 60 nm nickel oxide powder into acetone to prepare a nickel oxide acetone dispersion with a nickel oxide content of 8 wt%. Soak delignified basswood in the nickel oxide acetone dispersion at a material-liquid mass ratio of 1:180, and soak for 30 minutes in a closed state to load nano nickel oxide on the surface of the basswood cell cavity, then take out and dry until the acetone is completely volatilized.

[0084] 3. The basswood chips loaded with nano-nickel oxide were loaded into an alumina crucible, placed in a high-temperature tube furnace, and carbonized under nitrogen protection. The nitrogen flow rate was first turned on and controlled at 250 mL / min, maintained for 30 minutes, and after the internal gas was evacuated, the temperature was raised to 500°C at a rate of 5°C / min for carbonization treatment for 20 minutes. The basswood chips were graphitized under the catalytic action of the oxidant nano-nickel oxide to obtain carbonized basswood chips. The surface resistance after nano-nickel oxide catalytic carbonization was 0.2Ω / cm.

[0085] 4. In a high-density polyethylene container, add lithium fluoride to 12 mol / L hydrochloric acid with a density of 1.2 g / mL to prepare an etching solution, with a material-liquid ratio of 2.5 g / 40 mL. Slowly add 25 μm Ti3AlC2 powder as a precursor to the etching solution under vigorous stirring at a speed of 11000 rpm / min, with a material-liquid mass ratio of 1:10. Etch Ti3AlC2 at 45°C for 36 hours.

[0086] 5. The etched MXene mixture was washed with deionized water for 5 times to remove excess acid in a high-speed centrifuge at a speed of 10,000 rpm / min, with each cycle lasting 5 minutes. After each centrifugation, the etched MXene was layered by vigorous shaking at a frequency of 0.05 Hz and an amplitude of 150 μm. The exfoliated MXene suspension was collected by collecting the supernatant of multiple centrifugation cycles.

[0087] 6. Add graphene powder with a particle size of 6 μm and a thickness of 4 nm into the MXene suspension with a material-liquid mass ratio of 1:80, perform ultrasonic dispersion in a water bath for 30 min, and magnetically stir for 8 h. The ultrasonic frequency is 120 KHz and the magnetic stirring speed is 1500 rpm / min to obtain a MXene-loaded graphene solid-liquid mixture, which is then dried to obtain a MXene-loaded graphene mixture.

[0088] 7. Add 1H,1H,2H,2H-perfluorooctyltrichlorosilane (C8H4Cl3F13Si>97.0%) to the epoxy resin with a mass ratio of 1:20, an epoxy resin solid content of 58%, and a viscosity of 700mPa.s. The epoxy resin is hydrophobically modified by perfluorooctyltrichlorosilane. A MXene-loaded graphene mixture with a mass ratio of 8:87 was added to a hydrophobically modified epoxy resin and stirred at a high speed (speed 3000 rpm / min) for uniform mixing. Then, an ammonia-modified curing agent SH-K700 (melting point 160°C, particle size 4.5 μm) with a mass ratio of 5wt% was added to the MXene / graphene-epoxy resin. The mixture was mixed by high-speed shearing (high-speed shearing speed of 4000 rpm / min, working head diameter of 100 mm) for 10 minutes to prepare a MXenes / graphene-epoxy resin mixed material. The mixed material was placed in a vacuum oven for 10 minutes to remove bubbles. A vacuum oven was used to ensure that the material properties, such as water loss, were controlled to be negligible to obtain a MXene / graphene-epoxy resin mixture.

[0089] 8. Place the MXene / graphene-epoxy resin mixed material in a high-pressure impregnation pot, immerse the carbonized basswood chips in the MXene / graphene-epoxy resin mixed material with a mass ratio of 30:80, and use the vacuum pressure method for impregnation. Vacuum treatment is performed before pressurization. The negative pressure in the impregnation pot is used to extract the air inside the conductive carbonized wood. The vacuum degree is 0.1 MPa and the time is 10 min. Then, pressurized impregnation is performed with a pressure of 1.0 MPa and a pressurization time of 0.5 h. After unloading the pressure, take it out and cure it at room temperature for 20 h to obtain a wood-based hydrophobic low-voltage electric heating composite material.

[0090] 9. The prepared electrothermal composite material has an ultra-low-voltage electrothermal effect. The applied voltage is 2-4V and the steady-state temperature is 56-124°C. The contact angle of the wood electrothermal composite material is 152-158°, and it has super-hydrophobic properties. At the same time, due to the synergistic effect of MXene and graphene, the thermal conductivity of the material is significantly improved, and the thermal conductivity coefficient is 0.61-0.83W / (mK). In addition, it has good flame retardant properties, and the first heat release rate peak is 68.55kW / m 2 , oxygen index 37.5.

[0091] Comparative Example 1:

[0092] The wood was not treated by (1) to (3), and the rest was the same as in Preparation Example 1, that is, the uncarbonized natural wood was directly used in the subsequent treatment.

[0093] The prepared composite material has an applied voltage of 2-4V and a steady-state temperature of 30-41°C. The contact angle of the wood electrothermal composite material is 118-125°. Since the wood has not been delignified, MXene and graphene cannot completely fill the wood cell cavity during the impregnation process, and a good conductive and thermal conductive channel cannot be formed inside the wood. The thermal conductivity is 0.24-0.28W / (mK). The contact angle is significantly reduced due to the moisture absorption of the uncarbonized wood frame, and the first heat release rate peak is 122.7kW / m 2 , oxygen index 27.4.

[0094] Comparative Example 2:

[0095] The delignified wood was not treated with (2), and the rest was the same as in Preparation Example 1, that is, the delignified wood without catalyst loading was subjected to subsequent treatment.

[0096] The prepared composite material has a steady-state temperature of 38-67°C when an applied voltage of 2-4V is applied, a contact angle of 134-142°, a thermal conductivity of 0.37-0.48W / (mK), and a first heat release rate peak of 89.73kW / m 2 , oxygen index 29.1. The degree of graphitization of delignified wood without catalyst loading is low, and the wood fails to provide assistance for thermal and electrical conduction channels.

[0097] Comparative Example 3:

[0098] The wood was not treated by (1), and the rest was the same as in Preparation Example 1, that is, the wood that had not been delignified was used for subsequent treatment.

[0099] The prepared composite material has an applied voltage of 2 to 4 V and a steady-state temperature of 33 to 58 ° C. The contact angle of the wood electrothermal composite material is 121 to 137 °. Since the wood has not been delignified, MXene and graphene cannot completely fill the wood cell cavity during the impregnation process, and a good conductive and thermal conductive channel cannot be formed inside the wood. After carbonization treatment, the wood is graphitized, and the thermal conductivity is 0.29 to 0.33 W / (mK). The peak value of the first heat release rate is 117.5 kW / m 2 , oxygen index 28.3.

[0100] Comparative Example 4:

[0101] The precursor was directly mixed with graphene without etching treatment. The rest was the same as Preparation Example 1, that is, graphene powder with a particle size of 4 μm and a thickness of 6 nm and Ti3AlC2 powder with a particle size of 25 μm were mixed in a mass ratio of 1:80 to obtain a MXene-graphene mixture, and the mixture was directly used in subsequent treatments.

[0102] The prepared composite material has a steady-state temperature of 42-86°C when the applied voltage is 2-4V, and the contact angle of the wood electrothermal composite material is 134-143°. Since the graphene and the graphene are not intercalated into MXene to form a close conductive synergy, the electrothermal effect is significantly reduced. The thermal conductivity is 0.37-0.57W / (mK), and the peak value of the first heat release rate is 100.25kW / m 2 , oxygen index 31.8.

[0103] Comparative Example 5:

[0104] The epoxy resin was not modified with silane, and the rest was the same as in Preparation Example 1.

[0105] The prepared composite material has a steady-state temperature of 55-108°C when an applied voltage of 2-4V is applied, a contact angle of 117-126°, a thermal conductivity of 0.54-0.76W / (mK), and good flame retardancy. The peak value of the first heat release rate is 72.34kW / m 2 , oxygen index 37.2. The interfacial bonding strength between the epoxy resin without silanization modification and the loaded graphene MXene and the wood frame was weakened, affecting the electrical and thermal conductivity of the composite material, and the surface failed to achieve a superhydrophobic effect.

[0106] It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. The present invention can be modified in various ways within the scope defined by the claims. New modifications obtained by combining different implementation methods or embodiments, as well as common technical means, etc., should also be considered to be included in the scope of the present invention.

Claims

1. A method for preparing a wood-based hydrophobic low-voltage electric heating composite material, It is characterized in that include: (1) adjusting the pH value of a 4-6 wt% NaClO2 aqueous solution to 4.8-5.2 by using 17-18 mol / L glacial acetic acid, immersing wood in the adjusted NaClO2 aqueous solution, wherein the material-liquid mass ratio is 1:(100-150), then treating the wood in a water bath at 80-85° C. for 5-7 h, taking the wood out, washing, and drying the wood to obtain delignified wood; (2) immersing the delignified wood in a nano-nickel oxide / acetone dispersion, wherein the mass ratio of the material to the liquid is 1:(100-180) and the mass ratio of the nano-nickel oxide / acetone is (8-10):(90-92), and then immersing the wood in a sealed state for 30-50 minutes to load the nano-nickel oxide on the surface of the wood, and then taking it out and drying it until the acetone is completely volatilized; (3) heating the nano-nickel oxide-loaded wood to a carbonization temperature of 300 to 500° C. at a rate of 5 to 7° C. / min under nitrogen protection for 20 to 30 min, so that the wood is graphitized under the oxidative catalytic action of the nano-nickel oxide to obtain conductive carbonized wood; (4) slowly adding Ti3AlC2 powder to an etching solution under vigorous stirring, wherein the mass ratio of the material to the liquid is (1-1.5):(10-12), wherein the etching solution is prepared by adding lithium fluoride to hydrochloric acid having a concentration of 11-13 mol / L, and the material-liquid ratio of lithium fluoride to hydrochloric acid is (2-4) g:(20-40) ml, and then etching is performed at a temperature of 45-50° C. for 24-36 hours to obtain an etching mixture; (5) The etching mixture is centrifuged and washed multiple times to remove the acid, and after each centrifugation, it is layered by vigorous shaking, and the supernatant after each layering is collected to collect the exfoliated MXene suspension; (6) adding graphene powder to the MXene suspension at a material-liquid mass ratio of 1:(50-80), then performing water bath ultrasonic dispersion for 30-40 min and magnetic stirring for 8-12 h, and drying to obtain a MXene-loaded graphene mixture; (7) adding the MXene-loaded graphene mixture to the 1H,1H,2H,2H-perfluorooctyltrichlorosilane-modified epoxy resin adhesive and stirring at high speed to uniformly mix, then adding a curing agent for high-speed shear mixing, and then removing bubbles from the mixture to obtain a MXene / graphene-epoxy resin mixture, wherein: The 1H,1H,2H,2H-perfluorooctyltrichlorosilane modified epoxy resin adhesive is prepared by mixing 1H,1H,2H,2H-perfluorooctyltrichlorosilane and epoxy resin adhesive in a mass ratio of 1:(15-20), wherein the epoxy resin solid content in the epoxy resin adhesive is 55-58%, the viscosity is 500-700mPa.s, The mass ratio of the loaded graphene mixture, 1H,1H,2H,2H-perfluorooctyltrichlorosilane modified epoxy resin adhesive and curing agent is (2-10):(85-92):(5-6); (8) The conductive carbonized wood is subjected to negative pressure treatment with a vacuum degree of 0.1 to 0.15 MPa for 10 to 15 min, and then the MXene / graphene-epoxy resin mixture is added while maintaining the negative pressure until the wood is submerged, with a mass ratio of (5 to 20):(50 to 100), and then vacuum pressure impregnation is performed with a pressure of 1.0 to 1.2 MPa for 30 to 60 min. After being taken out, the mixture is cured at room temperature to obtain a wood-based hydrophobic low-voltage electrothermal composite material.

2. The preparation method according to claim 1, wherein In the above (2), the particle size of nano nickel oxide is 20 to 60 nm.

3. The preparation method according to claim 1, wherein In (4), the particle size of Ti3AlC2 powder is 0.5 to 25 μm, and / or Ti3AlC2 powder was added into the etching solution at a rate of 0.1 g / 10 s.

4. The preparation method according to claim 1, wherein In the above (4), the violent stirring speed is 10000 to 12000 rpm / min.

5. The preparation method according to claim 1, wherein In (5), a high-speed centrifuge is used to add deionized water to perform centrifugal washing for more than 5 times to remove acid, the centrifugal speed is 8000-10000 rpm / min, and each centrifugal treatment is 5-6 minutes, and or The frequency of violent oscillation is 0.05-0.1 Hz, and the amplitude is 100-150 μm.

6. The preparation method according to claim 1, wherein In (6), the graphene powder has a particle size of 1 to 6 μm and a thickness of 1 to 4 nm, and / or The ultrasonic frequency is 120-130 KHz, and the magnetic stirring speed is 800-1500 rpm / min.

7. The preparation method according to claim 1, wherein In the above (7), the high-speed stirring speed is 3000 to 5000 rpm / min.

8. The preparation method according to claim 1, wherein In (7), the curing agent is an ammonia-modified curing agent, and The high-speed shearing speed is 2000-4000rpm / min, the working head diameter is 90-100mm, and the time is 10-20min.

9. The preparation method according to claim 1, wherein The wood is basswood, with a density of 0.55-0.62g / cm 3 , thickness 0.25 ~ 4.0mm, surface resistance 0.15 ~ 0.22Ω / cm after nano nickel oxide catalytic carbonization.

10. A wood-based hydrophobic low-voltage electric heating composite material prepared by the preparation method according to any one of claims 1 to 9.